Tingkat Pengembalian (Return), Risiko, dan Koefisien Variasi pada Saham Syariah dan Saham Nonsyariah - Hadinata, Sofyan (IAIN Kudus, 2018)
The purpose of this study is to analyze the differences in the rate of return, risk, and coefficient of variation between sharia shares and non-sharia shares. This study uses a quantitative approach with the Mann-Whitney U Test. The population of this study is companies listed on the Indonesia Stock Exchange in 2017. Sharia shares refer to companies that listed in the Jakarta Islamic Index (JII) in the period 2017. The selection of samples uses purposive sampling. There are 24 sharia shares issuers, while non-Islamic shares are 8 issuers. The results of the study show that there is no difference in the level of weekly returns between sharia and non-sharia shares. As for the risks and the coefficient of variation statistically there is a difference between sharia shares and non-sharia shares